Pharmaceutical and Personal Care Products (PPCPs) in the environment: Plant uptake, translocation, bioaccumulation, and human health risks - Keerthanan, S.; Jayasinghe, Chamila; Biswas, Jayanta Kumar; Vithanage, Meththika (Critical reviews in environmental science and technology, 2021)
Pharmaceutical and personal care products (PPCPs) are considered as emerging contaminants (ECs) in the environment due to their known or suspected adverse ecological effects and human health risks. Wastewater, compost, and manure application release PPCPs into the agricultural soil systems. Since the plants can take up such ECs, they are considered as a primary window of human exposure to the PPCPs via the route of consumption of contaminated plants. This may lead to deleterious human health effects. However, as PPCPs are of various kinds, differential uptake and bioaccumulation in the plant have recently received research interest. Therefore, the present article reviewed the occurrence of PPCPs as antibiotics, anti-inflammatory drugs, hormones, cytostatic drugs, contrast media, β-blockers, blood lipid regulators, antiepileptic drugs, antimicrobials, ultra-violet filters, preservatives, insect repellents, and synthetic musks in the environment by assembling the literature. Moreover, plant uptake and translocation under the realistic and greenhouse condition, and the factors influencing the uptake and translocation through the plants are explicitly demonstrated in this review. Also, the human risk connected with the consumption of the contaminated plants and the research gap areas were investigated with future perspectives.